Epidemiology of hereditary anemias in Saudi Arabia - Alharbi, Shada Murshed; Alshaiti, Jawad Hussain; Ghazwani, Jamila Mofareh; Ghazwani, Afia Mofareh; Alshahrani, Nawaf Mohammed; Banjar, Mohammad Yosof; Alqahtani, Hager Saleh; Alkathiri, Saleh Hamdan; Alhamyani, Razan Abdullah; Althumairy, Abdulsalam Ibrahim; Amer, Mohammed Mustafa Al (International Journal Of Community Medicine And Public Health, 2021)
The prevalence rates of hereditary anemias in Saudi Arabia are remarkably high when compared to other countries. For instance, estimates show that the prevalence of thalassemia constitutes one of the highest rates globally. Furthermore, it has been demonstrated that epidemiology significantly differs between the different regions across the Kingdom. Therefore, many epidemiological investigations were conducted. In this context, it has been demonstrated that the prevalence of thalassemia ranges from 0.4% to 5.9% in the Northern and Eastern regions, respectively. In the present literature review, we have discussed the different findings of epidemiological studies that studied the epidemiology of hereditary anemias in Saudi Arabia. We mainly discussed the epidemiology of glucose-6-phosphate dehydrogenase deficiency (G6PD), sickle cell disease, and thalassemia. Recent evidence indicates that the trends of β-thalassemia are significantly decreasing over the past years. On the other hand, it has been demonstrated that the prevalence trends of sickle cell disease is constant over the past years. G6PD is also highly prevalent in Saudi Arabia. However, recent evidence is lacking in the literature and needs to be updated by future investigations. Consanguineous marriage has been reported to be an important risk factor for the high prevalence of β-thalassemia and sickle cell disease across the Kingdom.